"Radiotherapy for thymic epithelial tumors: What is the optimal dose? A systematic review.". (May 2022) - Angrisani, A.; Houben, R.; Marcuse, F.; Hochstenbag, M.; Maessen, J.; De Ruysscher, D.; Peeters, S.
Highlights: Thymic epithelial tumors(TETs) often require a multimodal approach, including RT. RT dose recommendations largely derive from old data, where 2D RT was widely used. This systematic review focused on the optimal dose for TETs with modern RT. 5 eligible studies reporting dose response were analyzed and synthesized. Current guidelines remain valid, this work might be an eye-opener fostering new data. Abstract: Thymic epithelial tumors (TETs) are rare thoracic tumors, often requiring multimodal approaches. Surgery represents the first step of the treatment, possibly followed by adjuvant radiotherapy (RT) and, less frequently, chemotherapy. For unresectable tumors, a combination of chemotherapy and RT is often used. Currently, the optimal dose for patients undergoing radiation is not clearly defined. Current guidelines on RT are based on studies with a low level of evidence, where 2D RT was widely used. We aim to shed light on the optimal radiation dose for patients with TETs undergoing RT through a systematic review of the recent literature, including reports using modern RT techniques such as 3D-CRT, IMRT/VMAT, or proton-therapy. A comprehensive literature search of four databases was conducted following the PRISMA guidelines. Two investigators independently screened and reviewed the retrieved references. Reports with < 20 patients, 2D-RT use only, median follow-up time < 5 years, and reviews were excluded. Two studies fulfilled all the criteria and therefore were included. Loosening the follow-up time criteria to > 3 years, three additional studies could be evaluated. A total of 193 patients were analyzed, stratified for prognostic factors (histology, stage, and completeness of resection), and synthesized according to the synthesis without meta -analysis (SWIM) method. The paucity and heterogeneity of eligible studies led to controversial results. The optimal RT dose neither for postoperative, nor primary RT in the era of modern RT univocally emerged. Conversely, this overview can spark new evidence to define the optimal RT dose for each TETs category.